Réponses

2013-09-28T21:12:23+02:00
10x+6=3x-1
10x-3x=-1-6
7x=-7  x=-7/7  x=-1

4(2x+5)=6x-3
8x+20=6x-3
8x-6x=-3-20
2x=-23  x=-23/2

7x+3(4+2x)=15+3x
7x+12+6x=15+3x
7x+6x-3x=15-12
10x=3  x=3/10



2(4x-5)=3+2(3x+2)
8x-10=3+6x+4
8x-6x=3+4+10
2x=17    x=17/2


6(x+2)=9x+3(6x+1)
6x+12=9x+18x+3
6x-9x-18x=3-12
-21x=-9  x=9/21=3/7
2013-09-28T21:22:17+02:00
10x + 6 = 3x -1
10x - 3x = -1 - 6
7x = -7
x = -1

4(2x + 5) = 6x - 3
4 * 2x + 4 * 5 = 6x - 3
8x + 20 = 6x - 3  
8x - 6x = -3 - 20
2x = -23
x = -11,5

7x + 3 (4 + 2x ) = 15 + 3x 
7x + 3 * 4 + 3 * 2x = 15 + 3x
7x + 12 + 6x = 15 + 3x
7x + 6x - 3x = 15 - 12
13x - 3x = 3
10x = 3
x = 0,3

2(4x - 5 ) = 3 + 2 ( 3x + 2 )
2 * 4x + 2 * (-5) = 3 + 2 * 3x + 2 * 2
8x + (-10) = 3 + 6x + 4
8x - 6x = 3 + 4 + 10
2x = 7 + 10
2x = 17
x = 8,5

6 ( x + 2 ) = 9x + 3 ( 6x + 1 ) 
6 * x + 6 * 2 = 9x + 3 * 6x + 3 * 1
6x + 12 = 9x + 18x + 3
6x - 9x - 18x = 3 - 12
6x + 9x = -9
15x = -9
x = -0,6
Pour le dernier, je ne suis pas sur, c'est peut-être faux donc je te préviens d'avance.
oui c'est faux car 6x-9x-18x= -21x et pas 15x